2022
DOI: 10.1177/11795549221109511
|View full text |Cite|
|
Sign up to set email alerts
|

GRHL2 Expression Functions in Breast Cancer Aggressiveness and Could Serve as Prognostic and Diagnostic Biomarker for Breast Cancer

Abstract: Background: Breast cancer (BC) is the most frequent malignancy in women worldwide and the leading cause of female cancer–associated death in the world. Grainyhead-like 2 ( GRHL2) is an important gene involved in human cancer progression. However, the role of GRHL2 in BC is unknown. Methods: In this study, we used in vitro experiments to verify the role of GRHL2 expression in BC progression. We used 14 databases to analyse the expression level of GRHL2 in BC and its prognostic and diagnostic value. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…33,34 GRHL2, which belongs to the GRHL transcription factor family, is related to cancer cell proliferation and invasion. 35,36 Moreover, GRHL2 was reported to promote T-cell proliferation by downregulating PD-L1 in gastric cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 GRHL2, which belongs to the GRHL transcription factor family, is related to cancer cell proliferation and invasion. 35,36 Moreover, GRHL2 was reported to promote T-cell proliferation by downregulating PD-L1 in gastric cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 GRHL2, which belongs to the GRHL transcription factor family, is related to cancer cell proliferation and invasion. 35 , 36 Moreover, GRHL2 was reported to promote T‐cell proliferation by downregulating PD‐L1 in gastric cancer tissues. 37 RPS29 was identified as a novel gene mutated in multicase Diamond‐Blackfan anemia families, 38 whose function on antitumor immunity is unknown and needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Cistrome DB analysis showed that GRHL2 has the greatest potential for SCIN binding. Our previous study [ 35 ] demonstrated that GRHL2 was more highly expressed in breast cancer tissues than in normal tissues, and the high expression of GRHL2 was associated with a worse prognosis for breast cancer patients. Although the ChIP qRT-PCR testified GRHL2 could directly bind to the promoter region of SCIN, the GRHL2 expression did not increase or decrease following RSRC2 upregulation or downregulation, suggesting RSRC2 has no regulatory effect on GRHL2.…”
Section: Discussionmentioning
confidence: 99%